Comment on "The Quadruple Bonding in C2 Reproduces the Properties of the Molecule". Issue 52 (12th December 2016) - Frenking, Gernot; Hermann, Markus
Abstract : Not the number of bonds but the strength of the total σ bonding in C2, which is suggested by several groups to be much weaker than in acetylene, is at the core of the controversy.